Multilingual Education Yearbook 2018 Internationalization, Stakeholders & Multilingual Education Contexts - Liyanage, Indika; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This volume examines how internationalization, stakeholders, and educational contexts have a reciprocal influence on multilinguals and their communities both as individual and collective variables. Therefore, the exploration of these variables and how they intersect and interact with worldwide phenomena like globalization, global citizenship, and responsive and responsible provisions of education are the central foci of this volume. Contributors from different parts of the world draw on analyses of various forms of data to foreground these foci with implications for effective multilingual education practices in their contexts, and beyond. The Multilingual Education Yearbook publishes high-quality empirical research on education in multilingual societies. It publishes research findings that, in addition to providing descriptions of language learning, development and use in language contact and multilingual contexts, will shape language education policy and practices in multilingual societies.
Internationalization of Higher Education, Mobility, and Multilingualism, Indika Liyanage -- Challenging Dominant Epistemologies in Higher Education: The Role of Language in the Geopolitics of Knowledge (Re)production, Adriana Díaz -- Media Representation of Attitudes to Multilingual Education: Local Language and Culture in Mainland China, Tao Xiong -- Reshaping Academic Writing in Internationalised Higher Education: A Contribution from Contrastive Rhetoric, Zosia Golebiowsky -- Academic English & EMI in the Asia Pacific: Complexities, Opportunities & Outcomes, Laura Gurney -- Internationalisation of Vietnamese Universities through English Medium Instruction (EMI): Practices, Tensions & Implications for Local Language Policies, Ly Thi Tran & Huong Thu Nguyen -- Trilingualism, National Integration, and Social Coexistence in Postwar Sri Lanka, Mufeeda Irshad -- Identity and Chinese Language Learning among Ethnic Minorities in Hong Kong, Gao Fang -- Internationalization and Multilingualism: Integration or Disintegration? Tony Walker.
Keywords: Language and languages; Multilingualism; Language policy; Language and languages-Study and; Literacy; Language Education; Multilingualism; Educational Policy and Politics; Language Policy and Planning; Language Teaching; Literacy